Mapping knowledge risks and implementing knowledge risk management The case study of Indonesia’s Financial and Development Supervisory Board - H Djabir Hamzah; Hj Nurdjanah Hamid; Isabella Ishak (Scientia Integritas Utama, 2023)
This study aims to describe the framework for implementing knowledge risk management by identifying knowledge risks based on their categories, RM-based KM practice designs and the techniques needed to be able to integrate them. This research uses a case study method with a qualitative approach in one of the government agencies in Indonesia, namely the Financial and Development Supervisory Board (BPKP). After applying KRM implementation techniques in the organization, it is known from the data analysis results that knowledge risk at the organizational level consists of three main categories, further subdivided into several knowledge risks. These three categories are included in the RM-based KM design (also known as knowledge risk management). This research still has limitations because it uses data sources from the 2008 organizational reports. However, this research is expected to be a reference and basis for designing a more effective KRM framework and implementation, adapted to the knowledge risks of public organizations.